Evaluating the Effects of Financial Ratios, Company Size and Growth Opportunities on Value Added Toward Food and Beverage Industry Listed in IDX - Dahlia, Dahlia; M, Nurmauludiana; Syarief, Prasetya G (MultiTech Publisher, 2023)
The research to analyze value added company using financial ratios, company size and growth opportunities. High company value can have a positive impact on the company. This research period starts from 2017 to 2021, where in this period a pandemic occurs due to the spread of the Covid-19 which causes a decline in the world economy. 140 registered companies with method used was purposive sampling using The SPSS data processing. Profitability, liquidity, Company Size and growth simultaneously influence company value. The coefficient of determination is 84.5% while 15.5% comes from other variables.